The Influence of Leadership, Motivation, and Compensation on Employee Performance at PT. LG Electronics - Panjaitan, Harry Patuan; Lumenta, Marshel Yordan; Febriyanto, Febriyanto; Suyono, Suyono; Rusilawati, Ermina; Kudri, Wan Muhamad (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to determine whether leadership, motivation and compensation an influence positive on the performance of employees of PT. LG Electronics.. The population in this study were all employees of PT. LG Electronics totaled 40 people. The sampling technique in this study is a census technique because the population is small. Thus, the number of samples in this study were 40 respondents. The method of analysis in this study is multiple linear regression and hypothesis testing using SPSS version 25. The results obtained by leadership influence positive and significant on employee performance motivation and compensation an influence positive and significant on the performance of employees of PT. LG Electronics. It is recommended to add or expand the sample in further research so as to obtain results that are more representative of the overall situation of employees. The next research period was enlarged to obtain a larger number of samples.